The Statistical Agencies of the Federal Government (Book). - Duncombe, Henry L. (The Accounting Review, 1950)
Reviews the book "The Statistical Agencies of the Federal Government—A Report to the Commission on Organization of the Executive Branch of the Government," by Frederick C. Mills and Clarence D. Long.